Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Animasi Terhadap Minat dan Hasil Belajar Siswa - Tri Wulandari; Rohimin Rohimin; Nurlaili Nurlaili; Gusti Rian Saputra (Nusantara: Jurnal Pendidikan Indonesia, 2023)
Using appropriate learning models is important in education. However, sometimes this aspect is often forgotten. So that it gives the impression that education practitioners are only "merely" teaching without considering the effectiveness of learning outcomes so that students can properly understand the material that has been prepared. So, the fundamental goals of education as mandated by the constitution cannot be achieved, especially during the current era of information technology disruption. Technological media's effectiveness can be an advantage if used appropriately as a learning media facility. This research aims to determine the effect of the problem-based learning model assisted by animation media on student interest and learning outcomes. The research method applied is experimental. The experimental design used by the researcher was a quasi-experiment which took a nonequivalent control group design.